The Evaluation of Distractor in English Semester Exam at Junior High School - Riza, Armilia; Sevrika, Hevriani; Elmiati, Elmiati; Tiara, Muthia (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to determine the quality of the items in the Odd Semester Final Examination Questions for English Subjects at SMP NEGERI 09 Padang for the 2022/2023 Academic Year. This research is quantitative descriptive. The Odd Semester Final Examination Items for English Subjects of SMP NEGERI 09 Padang consist of 50 multiple choice questions. This type of research is descriptive quantitative research. The participants of this study were 70 students of class VIII at SMP N 09 Padang which were determined through simple random sampling technique. This instrument is documentation of student answer sheet and key answer. From the data analysis the researcher can conclude that in terms of the effectiveness of the distractor, there are 19 items (38%) belonging to the very good and 15 items (30%) categories, 11 items (22%) including the sufficient category, 3 questions (6%) including the poor category, and 2 questions (4%) the questioners fall into the bad category